Risk Mitigation of Murabahah Financing for Teacher Certification at BPRS Metro Madani KCWest Garlic Bones - Mega, Mega Karlina Agustin; Noorikha Pandayahesti Saputeri; Warsiyah (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
Murabahah financing for teacher certification is a form of financing based on sharia principles in order to help teachers to obtain certification as part of increasing their professional competence. This research journal aims to find out how risk management is implemented in murabahah financing for teacher certification (Sergu) and how banks try to deal with bad customer financing. The object of this research is PT. BPR Syariah Metro Madani KC Tulang Bawang Barat. The method used isqualitative approach, type of field research (Field Research). The results of this research arerisk control at PT. BPR Syariah Metro Madani KC Tulang Bawang Barat has been managed well and in accordance with Standard Operating Procedures (SOP), which includes risk identification, risk measurement, risk monitoring and risk control.Customers duplicate teacher certification, bank (payroll accounts), late disbursement of certification funds from the government, teachers or customers are fired from their jobs while the financing process is still pending, or the government revokes certification funds.Implementation of risk management at PT. BPR Syariah Metro Madani KC Tulang Bawang Barat has been carried out by PT. BPR Syariah Metro Madani KC Tulang Bawang Barat starting from the implementation of market risk handling, credit risk and operational risk has been implemented in accordance with the handling program procedures implemented by the bank, it has been implemented in accordance with the risks that arise, the target to be achieved in handling financing risk management has been achieved.